Critical Analysis of Social Cognitive Learning Theory and Its Implementation in Elementary Schools - Widodo, Arif; Astuti, Budi (Balai Publikasi Indonesia, 2024)
This article aims to provide a critical analysis of Social Cognitive Learning Theory, explore its relevance in the elementary school context, and explore the challenges and potential for its implementation in the basic education environment. This research uses a literature study method with a focus on critical analysis of social cognitive learning theory and its implementation in elementary schools. Identification of library sources is carried out through literature searches in academic databases such as PubMed, Google Scholar, and digital libraries. The search results show that the main concepts of social cognitive learning theory, such as observational learning and modeling, can be applied effectively in elementary schools. Adaptation of Concepts to Children's Learning Stages Based on literature searches, it shows that the main concepts of social cognitive learning theory can be adapted well to children's learning stages in elementary school. The use of peer modeling has also proven effective in creating an inclusive learning environment. Search results related to the main challenges in implementing social cognitive learning theory in elementary schools found resistance to change and limited teacher resources. From the results of literature searches and comparisons with related research, it can be concluded that social cognitive learning theory has great potential to be applied effectively in elementary schools. Key concepts can be adapted well, and their implementation provides both challenges and opportunities. To overcome these challenges, it is important to consider individual student differences, overcome resistance to change, and ensure adequate use of resources